THE EFFECTIVENESS OF IMPLEMENTING SUMMARY WRITING TO IMPROVE STUDENTS’ READING COMPREHENSION - Hukom, Salmon J; Ferdinandus, Marcy S (Prodi Pendidikan Guru Sekolah Dasar (PGSD) FKIP Universitas Pattimura, 2024)
Students’ reading comprehension cannot be measured only by answering the questions, but it could be seen through summary writing as a product of integrating reading and writing skills. This study aims to see the effectiveness of implementing summary writing in improving students’ reading comprehension. There were 35 students as a sample and the research employed Experimental research with pre-test and post-test used to take the data. The description of statistics and inferential statistics were used to analyze the data, and the SPSS program also was used in the process of data analysis. The results show that the maximum pre-test score is 2.000, while the maximum post-test score is 4.000. Furthermore, the mean score of the pre-test is 1.890 with a deviation standard is 0,323, whereas the mean score of the post-test is 3,030 with a deviation standard is 0,453. After doing the requirement test of normality and homogeneity, the mean difference test is done by using the Mann-Whitney Test (assumption that data is not normal) with the SPSS program. The result of the Mann-Whitney Test shows that the significance value is smaller than 0,05 means that H1 is accepted. To sum up, this indicates that there are significant changes between the data in the pre-test and post-test after getting treatment using summary writing to improve students’ reading comprehension.